Longitudinal study evaluating postural balance of young athletes - Steinberg, N.; Nemet, D.; Pantanowitz, M.; Zeev, A.; Hallumi, M.; Sindiani, M.; Meckel, Y.; Eliakim, A. (Perceptual and Motor Skills, 2016)
Repeated anaerobic conditions during athletic performance may cause general and local fatigue that result in postural balance deficit. Evidence suggests that improved postural balance during athletic training may decrease the risk for fallings and traumatic injuries among athletes. Twenty athletes (12 girls, 8 boys) and 20 controls (12 girls, 8 boys) ages 10-15 years participated in the current study. All athletes were active in an 8-month physical activity program, 3 times per week for 90 min., specific to basketball, soccer, or athletic training. The control children participated in physical education at school only, with no involvement in organized extracurricular sports. All participants were evaluated for postural balance in three assessments over one year (at 4-mo intervals); the Interactive Balance System machine (Tetrax device) was used to assess balance at three test times (pre-, post-, and 10 min) after a session of a repeated sprint anaerobic test, consisting of 12 x 20 m run starting every 20 sec. The athletes had better postural balance than controls. There were different group patterns of change over the sessions; a significant interaction of session and group indicated that postural balance of the groups differed. The contribution of low sway frequencies (F1) and high sway frequencies (F6) differed between the controls and the athletes group. Results suggested that although athletes had better postural balance, improvement should be encouraged during training over the sessions and seasons, with special awareness of the balance deficit that occurs immediately after anaerobic stress and at the end of the season, to decrease the risk of injuries. ABSTRACT FROM AUTHOR